Novel Molecule Nell-1 Promotes the Angiogenic Differentiation of Dental Pulp Stem Cells - Li, Mengyue; Wang, Qiang; Han, Qi; Wu, Jiameng; Zhu, Hongfan; Fang, Yixuan; Bi, Xiuting; Chen, Yue; Yao, Chao; Wang, Xiaoying (Frontiers in Physiology, 2021)
Introduction: This work aimed to reveal the crucial role of Nell-1 in the angiogenic differentiation of human dental pulp stem cells (DPSCs) alone or co-cultured with human umbilical vein endothelial cell (HUVECs) in vitro and whether this molecule is involved in the pulp exposure model in vivo. Methods: Immunofluorescence was conducted to ascertain the location of Nell-1 on DPSCs, HUVECs, and normal rat dental tissues. RT-PCR, Western blot, and ELISA were performed to observe the expression levels of angiogenic markers and determine the angiogenic differentiation of Nell-1 on DPSCs alone or co-cultured with HUVECs. Blood vessel number for all groups was observed and compared using immunohistochemistry by establishing a rat pulp exposure model. Results: Nell-1 is highly expressed in the nucleus of DPSCs and HUVECs and is co-expressed with angiogenic markers in normal rat pulp tissues. Hence, Nell-1 can promote the angiogenic marker expression in DPSCs alone and co-cultured with other cells and can enhance angiogenesis in the pulp exposure model. Conclusions: Nell-1 may play a positive role in the angiogenic differentiation of DPSCs.